Electrical monitoring of organic crystal phase transition using MoS2 field effect transistor. Issue 6 (22nd February 2023) - Boulet, Ilan; Pascal, Simon; Bedu, Frederic; Ozerov, Igor; Ranguis, Alain; Leoni, Thomas; Becker, Conrad; Masson, Laurence; Matkovic, Aleksandar; Teichert, Christian; Siri, Olivier; Attaccalite, Claudio; et al.
Abstract : MoS2 transistors enable fast and accurate detection of structural modifications that occur during phases transitions of the quinoidal zwitterions layer. Abstract : Hybrid van der Waals heterostructures made of 2D materials and organic molecules exploit the high sensitivity of 2D materials to all interfacial modifications and the inherent versatility of the organic compounds. In this study, we are interested in the quinoidal zwitterion/MoS2 hybrid system in which organic crystals are grown by epitaxy on the MoS2 surface and reorganize in another polymorph after thermal annealing. By means of field-effect transistor measurements recorded in situ all along the process, atomic force microscopy and density functional theory calculations we demonstrate that the charge transfer between quinoidal zwitterions and MoS2 strongly depends on the conformation of the molecular film. Remarkably, both the field effect mobility and the current modulation depth of the transistors remain unchanged which opens up promising prospects for efficient devices based on this hybrid system. We also show that MoS2 transistors enable fast and accurate detection of structural modifications that occur during phases transitions of the organic layer. This work highlights that MoS2 transistors are remarkable tools for on-chip detection of molecular events occurring at the nanoscale, which paves the way for the investigation of other dynamical systems.